56 High serum parathyroid hormone level is independently associated with carotid intima-media thickness in older patients undergoing invasive management of non-st elevation myocardial infarction. (5th June 2017) - Beska, Benjamin; Neely, Dermot; Datta, Harish; Gu, Sophie Zhaotao; Batty, Jonathan; Sinclair, Hannah; Ford, Gary; Qiu, Weiliang; Kunadian, Vijay
Abstract : Introduction: Serum parathyroid hormone (PTH) levels, which are intimately linked to vitamin D status, are associated with an increased risk of cardiovascular events and mortality and may directly influence atherogenesis. Elevated carotid intima-media thickness (CIMT) is a non-invasive marker of subclinical atherosclerosis and is associated with cardiovascular disease, providing predictive power above traditional risk factors. The association between PTH levels and CIMT was evaluated in older patients undergoing invasive management of non ST-elevation acute coronary syndrome (NSTEACS). Methods: High-risk older patients (n=160, aged 65 years) attending a tertiary centre for invasive management of NSTEACS had CIMT of the left and right posterior carotid artery measured using B-mode ultrasound (Vivid-I®, GE Healthcare). The largest CIMT measurement was used for analysis. Serum PTH was measured by electrochemiluminescent immunoassay. Statistical modelling was performed using multiple regression, controlled by the hierarchical addition of a priori selected potential confounders. Results: Mean age was 80.4±4.0 years (64.7% male). Median PTH level was 5.6 pmol/L [IQR 4.0–6.8 pmol/L]. A significant relationship existed between logarithmically transformed serum PTH and CIMT (regression coefficient (B)=0.230, standard error of B(SEB)=0.086, standardised regression coefficient (&Icaron;²)=0.208, p=0.008) (Figure 1). The association was unchanged after adjustment for age, sex, glomerular filtration rate, body mass index, smoking status, hypertension and hypercholesterolemia (B=0.219, SEB=0.94, β=0.199, p=0.021). Addition of serum vitamin D resulted in a<10% change in the regression coefficient of PTH (β=0.199 to β=0.213, 7.0%) and was not a significant predictor of CIMT (p=0.209), suggesting that the relationship was not mediated by vitamin D. Conclusion: In this high-risk older cohort, high serum PTH levels are associated with increased CIMT independent of traditional atherosclerotic risk factors.